Science Education in the 21st Century 2020
DOI: 10.1007/978-981-15-5155-0_2
|View full text |Cite
|
Sign up to set email alerts
|

Representations of Nature of Science in New Korean Science Textbooks: The Case of ‘Scientific Inquiry and Experimentation’

Abstract: Nature of science (NOS) is becoming a core component of both science education research and curriculum policy around the globe. In particular, how textbooks should portray NOS aspects have been of keen interest to science educators. This chapter outlines the background and motivations for Korea's new compulsory subject, scientific inquiry and experimentation (SIE), and analyses how textbooks for this subject present NOS aspects using historical episodes. The aim is to help textbook authors and policymakers by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Numerous studies (Niaz, 1998;Rodriguez & Niaz, 2004;Niaz & Coştu, 2009, McDonald & Abd-El-Khalick,2017Yang et al, 2020) revealed the importance of content presentation. Their common conclusion was that there seems no effort to prepare science textbooks in science teacher education programs to improve prospective teachers' understanding of the NOS.…”
Section: Science Textbooks and Teaching Of The Nosmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies (Niaz, 1998;Rodriguez & Niaz, 2004;Niaz & Coştu, 2009, McDonald & Abd-El-Khalick,2017Yang et al, 2020) revealed the importance of content presentation. Their common conclusion was that there seems no effort to prepare science textbooks in science teacher education programs to improve prospective teachers' understanding of the NOS.…”
Section: Science Textbooks and Teaching Of The Nosmentioning
confidence: 99%
“…A recent study conducted by Yang et al (2020) focused on how NOS is represented and demonstrated by the science textbooks used in Korean schools. Their analysis framework is Erduran & Dagher's (2014) RFN view which is a re-conceptualized form of Irzik & Nola's (2011) FRA view.…”
Section: Science Textbooks and Teaching Of The Nosmentioning
confidence: 99%
See 3 more Smart Citations